2011
DOI: 10.1007/s00240-011-0411-9
|View full text |Cite
|
Sign up to set email alerts
|

Can the CT planning image determine whether a kidney stone is radiopaque on a plain KUB?

Abstract: Almost all kidney stones are CT positive. Before a CT scan can be done a CT planning image (CTI) is generated in order to select the exact scanning area. The CTI looks approximately like a normal kidney-ureter-bladder abdominal radiography (KUB) but with reduced quality. It has been used as a guide, assuming that if the kidney stone could be seen on the CTI the kidney stone also would be visible on a conventional plain KUB (radiopaque). From the perspective of diagnosis and treatment as well as follow-up it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Coronal images are more accurate for assessing crania-caudal stone dimension. Recently, there have been reports on the prediction of the SP of ureteral stones using size and area calculations from coronal images performed with multidetector CT (8)(9)(10)(11)(12). These studies reported better predicting rates than studies performed using axial CT images.…”
Section: Resultsmentioning
confidence: 96%
“…Coronal images are more accurate for assessing crania-caudal stone dimension. Recently, there have been reports on the prediction of the SP of ureteral stones using size and area calculations from coronal images performed with multidetector CT (8)(9)(10)(11)(12). These studies reported better predicting rates than studies performed using axial CT images.…”
Section: Resultsmentioning
confidence: 96%
“…For functional exercise and nutritional support, patients were encouraged to perform activities such as climbing stairs as early as possible under the guidance and help of medical staff. Parenteral or enteral nutritional support was given in combination with the patients' own physical condition, to increase the resistance of patients and lay a good foundation for postoperative recovery [ 17 ]. For dietary nursing, medical staff should instruct patients to drink water and carbohydrates 2 hr before surgery to improve preoperative discomfort symptoms.…”
Section: Methodsmentioning
confidence: 99%